Multifractal analysis for seismic wave in Kathmandu valley after Gorkha Earthquake-2015, Nepal - Tiwari, B. R.; Xu, J.; Adhikari, B.; Chapagain, N. P. (Journal of Nepal Physical Society, 2020)
We applied the multiscale signal processing technique, the Wavelet Transform Modulus Maxima (WTMM) to characterize high frequency properties of strong motion waveforms, in particular the temporal distribution and strength of singularities in Gorkha earthquake, 25th April 2015. We first explored their relation to earthquake data source. Then we applied the WTMM analysis to strong motion recordings. These showed that the timing and exponent of singularities measured by the WTMM method on the ground motion wave field are directly related to the position and exponent of assumed initial stress singularities on the fault plane. We found strong motion recordings at near the epicenter site have very high multifractality than far sites. Some differences and similarities among sites were successfully detected.